PENERAPAN METODE PETA PIKIRAN DALAM MENULIS ESAI MAHASISWA SEMESTER V STKIP YDB LUBUK ALUNG - Irawati Rahman; Dwi Mutia Chan (Ta'dib, 2016)
AbstractThis research is based on several problems found in students’ writing; (1) the structure of students’ essay is not complete; (2) the use of languge is not communicative; (3) the paragraph development is not coherent; and (4) the title of the essay is not appropriate. This reseach aims at implementing mind mapping technique in writing an essay. Mind mapping is a technique of teaching writing to help students map their idea in writing an essay. This research used quantitative research. The research sample was the fifth semester students of STKIP YBD Lubuk Alung registered in 2015/2016 academic year. The result of this research shows that mind mapping technique could increase students’ writing. This is indicated by the increase of students’ score after applying mind mapping technique. 25 students (92.6%) got very good score and 2 others (7.43%) got good score. Based on this finding, it is suggested for English teachers to use mind mapping technique to improve students’ writing skill.Kata Kunci: penerapan, teknik mind mapping, keterampilan menulis esai